Efektivitas Produksi Biogas Mini Dari Limbah Dapur (KW) Dan Kotoran Sapi (CM) - binti Mat Zuini, Zazurah; binti Zulkifli, Ernie (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2024)
Biogas is renewable energy. It is a free gas produced from kitchen waste (KW) and cow dung (CM). This can be used as an effective tool for households and communities to manage waste intelligently and use renewable energy. This is free gas produced from KW and CM. The effectiveness of mini biogas from KW and CM includes efficiency in waste management, energy generation, environmental benefits, cost effectiveness and socio-economic impact. The technology provides long-term answers to challenges, leading to a greener and more sustainable future. The use of biogas has emerged as a promising alternative energy source in efforts to find sustainable and environmentally friendly solutions. It is a flexible fuel produced through Anaerobic Digestion (AD) of organic materials as a waste management tool. Mini biogas generators demonstrate a feasible and effective process in converting waste streams into useful energy by exploiting the potential of natural recycling systems. It is also a colorless, flammable gas mixture produced from organic waste products. The methane (CH4) content contributes 50-70 percent and carbon dioxide (CO2) in the biogas composition. The total volume of gas we obtained was 73 ml, the combined percentage was 73%, and the presence of CH4 gas in the mixture was effective with the flame. It can be used for cooking and power generation, and process waste is recycled as the Sustainable Development Goals (SDGs) advance.